Defect generation in multi-stacked InAs quantum dot/GaAs structures - Roh, CH; Park, YJ; Kim, KM; Park, YM; Kim, EK; Shim, KB (ELSEVIER SCIENCE BV, 2001)
InAs self-assembled quantum dots (SAQDs) were grown on GaAs(1 0 0) substrates using a molecular beam epitaxy (MBE) technique. The InAs QDs were multi-stacked with 6,10 and 15 layers in which 2 monolayer (ML) thick InAs QD layers and 20 ML thick GaAs spacers were alternately positioned. The nanostructural features of the QD multi-stacked layers were characterized by scanning transmission electron microscopy (STEM). The QDs were well formed vertically up to 6-7 layers in each multilayered structure. Additionally, stacking faults, "volcano-like" defects and defects of an asymmetrical down triangular shape (ADTS) were observed in the 10- and 15-layer InAs QD/GaAs samples. The generations of these defects are discussed mainly in terms of the interdiffusion of the III-group atoms, Ga and In. The subsequent strain relaxation and gradient of surface chemical potential are suggested to be the cause of these defects. (C) 2001 Published by Elsevier Science B.V.
Keywords: MOLECULAR-BEAM EPITAXY; SELECTIVE FORMATION; FORMATION MECHANISM; DOT LASER; GAAS; ISLANDS; GROWTH; LAYER; ORGANIZATION; GAAS(001)